Physicochemical Properties and Fertility Assessment of Soils in Foumban (West Cameroon) - Vivien Piercy Lotse Tedontsah; Michel Bertrand Mbog; Gilbert François Ngon Ngon; Robert Christel Edzoa; Bernard Tassongwa; Dieudonné Bitom; Jacques Etame (Applied and Environmental Soil Science)
Foumban is located in the West Cameroon Highlands, precisely in the Noun Valley. Given the low productivity recorded in this locality, this study aims to assess the state of soil fertility in this locality in order to redefine the major agro-ecological complexes in Cameroon. In order to achieve this objective, ninety (90) soil samples of this area were studied in order to determine their physicochemical parameters, namely, soil organic carbon (OC), total nitrogen (N), available P, total P, exchangeable cations (Ca, Mg, K, and Na), cation exchange capacity (CEC), and pH of water. The results obtained showed that the soils of Foumban present three classes of fertility, namely: class one (01) includes soils with a good level of fertility that are plaggic hortic NITISOLS (arenic) (NIpha), the chernic arenic UMBRISOLS (UMca), umbric arenic FERRALSOLS (Flua), mollic fragic NITISOL (hortic) (NImfh), the cambic hortic FERRALSOLS (plaggic) (FLchp) on basalts, umbric pisoplinthic PLINTHOSOLS (haplic) (PLuph), nitic CHERNOSOLS (pretic) (CHnp), and cambic FRAGISOLS (plaggic) (FGcp) with an area of about 528.71 Km2. Class two (02) includes soils with an average level of fertility that are the pretic UMBRISOLS (UMp) only, on an area of about 226.14 Km2. Class three (03) includes soils with a poor level of fertility that are the hortic FERRALSOLS (plaggic) (FLchp) on trachytes and the cambic FRAGISOLS (plaggic) (FGcp) with an area of about 38.47 Km2. Principal component analysis (PCA) has revealed that the parameters that control fertility in Foumban soils are C/N, pHeau, Ca, CEC, OM, P, and Mg. An amendment of these soils in organic fertilizer (fluent, compost, and manure) would facilitate the formation of the clay-humus complex; thus, allowing good retention of water in the soil.